Business models for Finnish biobanks - Hytönen, Heta (My University, 2015)
This study concentrates on developing a suitable business model for Finnish biobanks, with particular emphasis on value creation to stakeholders. The sub-objective of this thesis are to map the commercial possibilities of biobanks and potential barriers for business development. The study approaches the subject from the biobanks’ as well as the stakeholders’ point of view, integrating their hopes and needs considering current and future co-operation into the findings. In 2013 the Biobank Act came into effect, after which six biobanks have been established and several other pending biobank projects are in process. There is relatively little research in regard to the commercial opportunities of this newcomer of the biomedical industry, and particularly in the Finnish markets. Therefore, the aim of this study is to partially fill the research gap of the commercial potential of biobanks and particularly outline the problematic elements in developing business. The theoretical framework consists of a few select theories, which depict business modeling and value creation of organizations. The theories are combined to form a synthesis, which best adapts to biobanks, and acts as a backbone for interviews. The empirical part of the study was conducted mainly by seven face-to-face interviews, and complemented by two phone interviews and an e-mail questionnaire with four responses. The findings consist mainly of the participants’ reflections on the potential products and services enabled by consumer genomics, as well as perceptions on different obstacles for biobanks’ business development. The nature of the study is tentative, as biobanks are relatively new organizations in Finland, and their operation models and activities are still molding. The aim is to bring to surface the hopes and concerns of biobanks’ representatives, as well as the representatives of stakeholders, in order to transparently discuss the current situation and suggestions for further development. The study concludes that in principle, the interviewees’ agree on the need for development in order not to waste the potential of biobanks; regardless, the participants emphasize different aspects and subsequently lean on differing methods.